2015
DOI: 10.3109/10717544.2015.1077291
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal delivery of tadalafil using a novel formulation

Abstract: The aim of this work was to investigate the transdermal gel loaded with tadalafil, a practically insoluble selective phosphodiesterase-5 inhibitor (PDE5) in order to improve the solubility and bioavailability. The solubility of tadalafil in mixed solution of hydroxypropyl-b-cyclodextrin (HPCD), polyethylene glycol (PEG) 400 and tween 80 (T2 solution) was 260.8 ± 4.3 mg/mL and that of tadalafil in modified T2 (M-T2) solution, which tadalafil was dissolved in 20% (w/v) HPCD at first and then mixture solutions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…where C d is the initial drug concentration in the donor compartment, and the slope is that of the cumulative amount of drug permeated versus the square root of time plot. The enhancement ratio (ER) was calculated by dividing the J ss of the optimised microemulsion system by that of the sildenafil suspension [4,19,20].…”
Section: Skin Permeation Studies Using Franz Diffusion Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…where C d is the initial drug concentration in the donor compartment, and the slope is that of the cumulative amount of drug permeated versus the square root of time plot. The enhancement ratio (ER) was calculated by dividing the J ss of the optimised microemulsion system by that of the sildenafil suspension [4,19,20].…”
Section: Skin Permeation Studies Using Franz Diffusion Cellsmentioning
confidence: 99%
“…It is available only in the form of tablets. Some studies have shown that sildenafil citrate or PDE inhibitor drugs can be administered topically [4][5][6][7]. The transdermal delivery of sildenafil citrate through a local tissue area could be considered as an alternative to the oral route, in order to avoid adverse effects, shorten the onset time, and sustain the therapeutic effects for longer periods [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a clear, viscous, nonvolatile, nonirritating, low-molecular-weight polyether compound composed of polyethylene and water. It is widely used as a solvent and permeation enhancer in transdermal formulations [25]. Tween 80, a nonionic surfactant, is a solubilizing agent for a variety of substances and is included in the formulation to enhance the solubility of nebivolol.…”
Section: Introductionmentioning
confidence: 99%
“…Topical and transdermal drug delivery can offer great potential for non-invasive and non-oral administration of poorly bioavailable therapeutic agents (Kalia et al., 2004 ; Chen et al., 2016 ; Jacobs et al., 2016 ; Zidan et al., 2016 ). Drug delivery through the skin has merits in improving patient compliance and avoiding gastrointestinal irritation and hepatic first-pass effect (Baek & Cho, 2016 ; Jain et al., 2017 ). Moreover, topical delivery can enhance the efficiency of drug targeting to the skin and adjacent tissues, while transdermal delivery can provide a constant systemic exposure profile, potentially reducing several side effects caused by fluctuating blood drug concentrations (Jung et al., 2015 ; Patel et al., 2016 ; Rao et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%